Impact model of urban development on steppic birds in natura 2000 spaces. (January 2020) - Gutiérrez, J.; Velázquez, J.; García-Abril, A.; Hernando, A.; Sánchez, B.; Gómez, I.
Highlights: Urbanization is a threat to biodiversity conservation. We quantified the effect of infrastructure and urbanization over steppic birds. This study can be used to support conservation plans based on habitat connectivity. Abstract: Urbanization is one of the agents that contribute most to habitat fragmentation and is therefore a threat to biodiversity conservation. Connectivity improvement is the adaptation strategy most often cited to address species conservation in a changing environment. Many studies of protection at local and regional level zones usually show separate portions of habitat, defining the protected area, but they do not provide guidance on where and how to act to preserve the habitat quality and connectivity of the populations, on a consistent scale with planning units. In this paper, the analysis of fragmentation-connectivity focuses on cereal steppes of the Jarama and Henares rivers (Spain) to study the habitat and connectivity of steppic birds populations into protected areas of the Natura 2000 network, quantifying the effect on this protected area and on the species of interest caused by the massive development of infrastructure and urbanization due to the expansion of Madrid metropolitan area. In this sense, the Great Bustard ( Otis tarda ) was used as a bioindicator, due to its high demand for habitat quality. The proposed methodology only needs to be based on data from wildlife sightings and land use. Once the variables (density, biophysics and urbanization) were defined, it was possible to determine the values of influence, applying them to generate the map of areas of probability of presence and movement of the Great Bustard. This can be used to support conservation plans based on habitat connectivity.